Health Lecturers and Students Views’ about Healthcare Workers’ as Healthy Lifestye Role Models: a Qualitative Study - Agustina Arundina Triharja Tejoyuwono (Universitas Muhammadiyah Yogyakarta, 2020)
Background: Health education institutions as producers of healthcare workers have a duty to demonstrate healthy lifestyles to the students as the future healthy role models. Objective: This research aimed to describe the views of health lecturers and students about their role and the effect of healthcare workers’ behavior as healthy lifestye role models. Method: An exploratory qualitative study with in-depth interviews was conducted in 2017. Six lecturers and five studentss were chosen as key informants, who were selected from the medicine, nursing, and health nutrition departments. We analyzed the data manually, by identifying categories then created into themes. Result: Healthcare workers were judged as a representative figure to demonstrate healthy lifestyles. Unhealthy lifestyle practice by healthcare workers was considered a violation of their responsibility. Furthermore, it will decrease the image and respect of healthcare workers which will cause people to trust less in the treatment process and health counseling, and finally, the society will imitate unhealthy lifestyles. Furthermore, in medical education, this influences lecturers’ self-efficacy in health counseling, causing guilty feelings and shame for not implementing a healthy lifestyle although they had already learned health science. Moreover, the students sometimes feel sadness and disappointment, since not all lecturers can become healthy lifestyle role models. Conclusion: Healthcare workers are role models of healthy lifestyles in society and expected to be in any setting. Therefore, they should appropriately respond to becoming someone who qualifies to be imitated and be a good example of a healthy lifestyle in society.